Exploration of Endophytic Bacteria from Benincasa hispida (Kundur) Plants Originating from Southeast Sulawesi and Their Antibacterial and Antibiofilm Activities against Staphylococcus aureus - Ekajayanti Kining; Efrita Bataragoa; Fitria Dewi; A. Ainun Nurfajrin (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
The main problem addressed is the increasing resistance of S. aureus, making it necessary to discover new bio-based antibacterial sources. This study aimed to isolate and identify endophytic bacteria from the leaves of B. hispida originating from Southeast Sulawesi, and to evaluate their antibacterial and antibiofilm activities against S. aureus using the disc diffusion method and crystal violet assay. The research methods included surface and internal tissue sterilization of the plant, isolation of bacterial colonies, Gram staining, metabolite extraction, bioactivity tests, and phytochemical assays. Results indicated one endophytic bacterial isolate with Gram-positive characteristics, and the endophyte extract demonstrated very strong antibacterial activity at a concentration of 200 microgram/mL (inhibition zone 22–23 mm, comparable to the positive control). The percentages of growth inhibition and biofilm degradation reached >80% and >70% respectively at the highest concentration. In conclusion, endophytic bacteria from B. hispida of Southeast Sulawesi have promising potential as a natural source of antibacterial and antibiofilm agents relevant for therapeutic development against S. aureus infections. Keywords: Benincasa hispida; antibacterial; antibiofilm; S. aureus; Kendari